BIOLOGICAL STATUS OF CATCHES FISH AND BOTTOM LONG LINE HOOK RATES OPERATED IN KAO BAY, HALMAHERA NORTH MALUKU PROVINCE (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Kao Bay on Halmahera Island has been intensively operated bottom longlines by small scale fisheries. The target of catch not only demersal fish which have economic value, but also caught various types of fish that is not of economic value. Fishing activities at one location continuously can affect the sustainability of these fish resources. The purpose of this study was to analyze: composition of fish species, level of gonadal maturity from the dominant target species, and compare the bottom longline hook rate based on the number of fishing lines. Survey method was used to collecting data. Data analysis includes: species composition, distribution of level gonadal maturity, and fishing rate. The results shows that the target fish catch consist of 18 species categorized into 4 groups. Fish composition: Nemipterus hexodon (53%), Lutjanus spp (22.2%), Luthrinus spp (11.1%), other catches (13.7%). While, side catches consist of 7 species, which are dominated by types of sharks with varying compositions. The proportion of gonad maturity is based on long class sizes: 54% Nemipterus hexodon  (22-23 cm), 50% Lutjanus spp (18-23 cm), Luthrinus spp 100% (20-27 cm). Hook rate number of fishing line 400 by 4.40 was higher compare to the number of fishing lines 300, 500, 600 and 700.